IMPLEMENTASI KEBIJAKAN PENATAAN RUANG TERBUKA HIJAU PUBLIK DI KELURAHAN TLOGOSARI KULON, KECAMATAN PEDURUNGAN KOTA SEMARANG - Santosa, Reza Agung; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
However, Public Open Green Space in Semarang City iss only 7.5% the law stipulates that Act every city must have a minimum 20% Open Green Space. This study describe about how the regulation of Open Green Space Planning in Semarang City is, Number 7 Year 2010 about Open Green Space Planning. The purpose of this study is to see how the Implementation of Open Green Space Planning in West Tlogosari is and What are the factors that influence the implementation of open green space of public in Semarang city. This Research is Qualitative Descriptive. Based on the result of the study shows that the implementation of open green space planning in Semarang City consist of planning, utilizing and controling. There are founded the obstacle factor of open green space planning in West Tlogosari, that are not achieving the 20% of Public Green Space, the high price of land, the competence of human resources, uneficient communication interagency, and awarness of society about the needs of public open green space. Semarang Municipal Goverment is suggested to achieve ‘short-term- target of 20% public Open Green Space area, negotiate the price of land with societies, provide training about the implementation of Open Green Space Planning, make the flexible coordination rules, and give information about the Open Green Space to the societies and create an activities to get participation of societies in Implementing of Open Green Space Planning in West Tlogosari, Distric Pedurungan, Semarang City.